Rehabilitative Effects of Virtual Reality Technology for Mild Cognitive Impairment: A Systematic Review With Meta-Analysis - Wu, Jinlong; Ma, Yudan; Ren, Zhanbing (Frontiers in Psychology, 2020)
Abstract Obsjective: To objectively evaluate the impact of virtual reality (VR) technology on the cognitive functions (overall cognitive ability, executive function, short-term memory, and delayed memory) of people with mild cognitive impairment (MCI). Data sources: From the start to October 28th, 2019, six databases were searched (Web of Science, PubMed, Scopus, Proquest, WanFang, CNKI). Study selection: 15 randomized controlled trials were analyzed. Data extraction: Two researchers independently conducted document retrieval, study selection, data extraction, and methodological quality evaluation. Data synthesis: A random effects model wass selected to combine effect sizes. The result of the meta-analysis indicates that VR significantly enhanced MCI patients’ overall cognitive ability (SMD=0.869) and executive function (SMD=1.083). Conclusions: The present meta-analysis verifies the potential rehabilitative effects of VRtechnology for mild cognitive impairment. Keywords: Mild Cognitive Impairment; Virtual Reality; Cognitive function